Monstress. Volume five, Warchild - Liu, Marjorie M.; Liu, Marjorie M.; Takeda, Sana (Image Comics, 2020)
"The long-dreaded war between the Federation and Arcanics is about to explode. Maika must choose her next steps: will she help her friends, or strike out on her own?"--Provided by publisher.